RELEVANCY OF RESEARCH EVIDENCE WITH THE SUCCESS OF ALQURAN MEMORISING: YOUNG HAFIZ MOTIVATIONAL APPROACH - Aslan Aslan (Jurnal Ilmu Pendidikan Islam, 2022)
This article discusses the evidence for the successful study of memorizing the Qur'an, which is shown to gain an understanding of the motivational approach of young hafidz. The author believes that memorizing the Quran is closely related to experience and studies that have given parents and parents confidence. Our data is obtained from literature such as published journals, books, and website data. Before getting the findings to this study, we first examine the data with a phenomenological approach, exploring as much data as possible to understand that answer. This study entirely relies on secondary data from the findings of previous work, and we design it in a descriptive qualitative study—data coming soon young people.com. Based on our study and discussion, we conclude that there is a very close relevance between the evidence of scientific studies on the memorization of the Qur'an project and the success of students reading the Qur'an. Thus, this finding should be a helpful input in efforts to improve the quality of studies and scientific reading and Hafiz of the Qur'an for the younger generation. Keywords: Relevancy, research evidence, memorizing the Quran, and motivational approach.